Моделирование отклика CdZnTe- и TlBr-детекторов для регистрации смешанного бета- и гамма-излучения - Скрыпник, А.И. (Технология и конструирование в электронной аппаратуре, 2015)
Выполнено моделирование функции отклика CdZnTe- и TlBr-детекторов на индивидуальные источники излучения ¹³⁷Cs и ⁹⁰Sr с помощью кода GEANT4. Получены спектры для случаев, когда перед детектором размещается бета-фильтр для поглощения электронов и без него. С помощью моделирования методом Монте-Карло найдена оптимальная толщина Al бета-фильтра для полного подавления конверсионных электронов в спектре ¹³⁷Cs. Также получена функция отклика TlBr-детектора на смешанный источник излучения (¹³⁷Cs+⁹⁰Sr). Виконано моделювання функції відгуку CdZnTe- і TlBr-детекторів на індивідуальні джерела випромінювання ¹³⁷Cs та ⁹⁰Sr за допомогою коду GEANT4. Отримано спектри для випадків, коли перед детектором розміщується бета-фільтр для поглинання електронів і без нього. За допомогою моделювання методом Монте-Карло знайдено оптимальну товщину Al бета-фільтра для повного заглушення конверсійних електронів в спектрі ¹³⁷Cs. Також отримано функції відгуку TlBr-детектора на змішане джерело випромінювання (¹³⁷Cs + ⁹⁰Sr) з бета-фільтром і без нього. The paper deals with the problems of measuring Fourier spectrum of signals in the base of discrete exponential functions. Methods and algorithms of sliding measurements of energy Fourier spectrum of signals on finite intervals were described. The invariance of current energy Fourier spectrum to moving discrete real signals (which are not periodic) were investigated. The authors identify a new effect of digital spectral analysis — the effect of non-invariance of the current energy Fourier spectrum. Theoretical and practical results of analysis of invariance of current energy Fourier spectrum of tonal components are shown. The conducted studies allow us: — to see in a new light the measurement results on finite intervals of current Fourier spectrum and the current energy Fourier spectra of signals; give a numerical estimate of the non-invariance of the current energy Fourier spectrum of real tonal components. — to increase the effectiveness of digital spectral analysis in its many applications, in particular, for solving the problems on detection and identification of hidden periodicities in such subject areas as radar, vibroacoustic diagnostics, passive sonar, biomedicine, etc.